MEMPREDIKSI FREKUENSI FUNDAMENTAL PADA MODEL SATELIT INASAT.1 PADA SUMBU X DENGAN MENGGUNAKAN METODA SPEKTRUM DAYA - Daryono Restu Wahono (National Institute of Aeronautics and Space - LAPAN, 2004)
The fundamental frequency of UUT can be predicted using power spectral density method with random signal input source. The test execution of INASAT 1 satellite shall meet the following standard of Indian Space Research Organisation (ISRO) in Polar Satellite Launch Vehicle (PSLV) auxiliary satellite user's manual a fundamental frequency in Lateral axis X 45 Hz. these values are with fixed boundary conditions at the spacecraft mounting interface and include the contribution of separation system. The test result of LAPAN satellite model INASAT.1 for X axis is predicted for fundamental frequency. It was detected that resonance frequency started at 80 Hz and peak accured at 120 Hz